How cognitively demanding is the urban niche? Reconsidering exaptation and habituation - Lily Johnson-Ulrich; Sofia Forss (Animal Cognition)
Abstract Urbanization is hypothesized to create a myriad of cognitive challenges for animals because it creates novel environmental conditions in evolutionary terms. The consensus is that these novel urban challenges act as drivers for increased cognitive abilities. However, scant empirical data validates the idea that urban environments are cognitively demanding relative to native ones. In this short communication we draw the attention to the fact that for some large-brained urban inhabitants the urban environment may instead provide “easy” exploitable niches, where these species can thrive because they already have the necessary cognitive tools in place. As such, evolutionary seen, such species are “exapted” to occupy a less challenging urban niche. As follows, while a species’ cognition may facilitate its persistence under urbanization, it does not necessarily mean that urban populations face selective or developmental drivers for improved cognition in urban living. We further point out the potential bias anthropogenic habituation can bring about when intraspecific comparisons are made between urban and nonurban populations and suggest that researchers must focus on precisely which species-specific aspects of the environment are novel when making predictions about the consequences of urbanization on cognitive traits.